Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/jsfa.4332
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of molecular distillation to concentrate ethyl esters of eicosapentaenoic (20:5 ω-3) and docosahexaenoic acids (22:6 ω-3) using simplified phenomenological modeling

Abstract: The theoretical model and the optimization give decision criteria about the operative conditions for reaching the highest yield during molecular distillation of ω-3 fatty acid ethyl esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…To construct and validate the ANN predictive model experimental data were used from Rossi et al (2011) along with theoretical concepts based on phenomenological laws.…”
Section: Description Of the Processmentioning
confidence: 99%
See 2 more Smart Citations
“…To construct and validate the ANN predictive model experimental data were used from Rossi et al (2011) along with theoretical concepts based on phenomenological laws.…”
Section: Description Of the Processmentioning
confidence: 99%
“…Rossi et al (2011) reported the EE composition squid Illex argentinus oil analyzed by gas chromatography. In that study, several fatty acids in significant amounts were detected.…”
Section: Description Of the Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Separating the oil's components by weight allows contaminates to be reduced far below industry standards. Current industrial applications include cosmetic applications, the concentration of omega-3 fatty acids (EPA and DHA) and corresponding esters in fish oil (Rossi et al, 2011), and contaminant removal. Additionally, Vitamin E (Pramparo et al, 2005), Vitamin A, cocoa butter, dimer acids, epoxy resins, lubricants, monoglycerides, insecticides, pharmaceuticals, perfumery and flavours, essential oils, Azadirachtin (Neem based pesticides) and its formulations as well as many other natural & herbal products have been distilled on an industrial scale using this process.…”
Section: Molecular Distillationmentioning
confidence: 99%
“…Many reports on the molecular distillation of fatty acid esters from sunflower and soybean esters (Pramparo et al, 2005), rapeseed fatty acid esters and tocopherols (Jiang et al, 2006), eicosapentaenoic (EPA) and docosahexaenoic acid ethyl esters (Brevik et al, 1997), and squid visceral oil ethyl esters (Liang & Hwang, 2000;Rossi et al, 2011) have been reported. Vázquez and Akoh (2010) reported a detailed study on the fractionation of short and medium chain fatty acid ethyl esters via short-path distillation that were obtained from a blend of coconut oil and dairy fat.…”
Section: Distillationmentioning
confidence: 99%